(untitled) (Mustansiria Dental Journal, 2018)
in vitro study to evaluate the effect of an at-home bleaching product on the surface hardness of three composite restorative materials. The aim of this study was to evaluate the effect of at-home bleaching on the surface hardness of the tooth colored restorative materials. Thirty specimens were prepared; 10 specimens of each material 5 specimens control of each group. All specimens were stored in distilled water at room temperature for 24 hrs before testing. A universal testing machine (Micromet micro hardness testers) was used for testing brinell surface hardness for the three groups& for every tested material. Three tested materials was assessed by ANOVA& further exploration between all possible paired combination of tested material was assessed by bonferroni adjusted t-test p value less than 0.05 was considered statistically significant . The statistical analysis showed that at home bleaching technique have statistically significant effect of the micro hardness of composite resin. At-home bleaching agents have a softening effect on some tooth colored restorative material, and the patient must be aware before using them.